Melanin‐Inspired Organic Electronics: Electroluminescence in Asymmetric Triazatruxenes. Issue 6 (1st May 2015) - Manini, Paola; Criscuolo, Valeria; Ricciotti, Laura; Pezzella, Alessandro; Barra, Mario; Cassinese, Antonio; Crescenzi, Orlando; Maglione, Maria Grazia; Tassini, Paolo; Minarini, Carla; Barone, Vincenzo; d'Ischia, Marco
Abstract: Invited for this month's cover is the group of Dr. Paola Manini from the University of Naples Federico II. The cover picture shows the concept underlying the design of a melanin‐inspired electroluminescent material for OLED devices. This article is part of a well‐structured research project aimed at imitating Nature's most enigmatic and fascinating functional pigments for the design and synthesis of innovative biomaterials for organic electronics applications. Read the full text of the article at 10.1002/cplu.201402444 . Abstract : " …︁to translate the unique physical–chemical properties of man's own natural pigments into the emerging fields of organic (bio)electronics and nanomedicine…︁ " Read more about the story behind the cover in the Cover Profile and about the research itself on page919 .